Dual-Station Integration Design of Shanghai Suburban Railway Demonstration Zone Line and Shanghai Metro Line 17 Xicen Station under Yangtze River Delta Integration Demand - FANG Yingli; ZHANG Yuan; LI Qin; XU Yue; ZHANG Bin; WANG Jinkun (Chengshi guidao jiaotong yanjiu)
［Objective］ Shanghai is the central city of the Yangtze River Delta integration, its Suburban Railway Demonstration Zone Line (shorted as D Zone Line)plays a significant strategic role in promoting the integration of the Yangtze River Delta. In combination with the Jiangnan characteristics and functional requirements of D Zone Line in terms of historical development, cultural attributes, and geographical features, Xicen Station is taken as a case study, the dual-station integration design and development strategy of D Zone Line Line station and the elevated subway station of Shanghai Metro Line 17 is introduced, aiming to provide a reference for the integration model of city railways and urban rail transit under the needs of the Yangtze River Delta integration. ［Method］ Several major challenges faced by the dual-station integration of Xicen Station, including engineering challenges, scale challenges, spatial challenges, and cognitive challenges, are analyzed. And by conducting demonstrations from three perspectives of architecture, structural design, and interior design, the design response strategies to several major and difficult issues are analyzed. ［Result & Conclusion］ Xicen Station integrates architectural design thinking into the design strategy of infrastructure. Through architectural controls (color, scale, space, modularity), structural deductions (large-span structures, structural phase and layering), and interior implementation (signage integration), it successfully defines a new paradigm for the highly integrated design of city railway stations and urban rail transit facilities. This not only enhances the overall efficiency of the integrated rail network but also provides passengers with a comfortable and convenient travel experience.